Aggregation-induced emission supramolecular organic framework (AIE SOF) gels constructed from tri-pillar[5]arene-based foldamer for ultrasensitive detection and separation of multi-analytes. Issue 33 (9th August 2019) - Wei, Tai-Bao; Ma, Xiao-Qiang; Fan, Yan-Qing; Jiang, Xiao-Mei; Dong, Hong-Qiang; Yang, Qing-Yu; Zhang, Yun-Fei; Yao, Hong; Lin, Qi; Zhang, You-Ming
Abstract : A novel aggregation-induced emission supramolecular organic framework (AIE SOF) constructed using tri-pillar[5]arene-based foldamer which could be used for the ultrasensitive detection of multi-analytes. Abstract : In this study, a novel aggregation-induced emission supramolecular organic framework (AIE SOF) with ultrasensitive response, termedFSOF, was constructed using a tri-pillar[5]arene-based foldamer. Interestingly, benefiting from the noise signal shielding properties ofFSOF as well as the competition between the cation⋯π and π⋯π interactions, theFSOF shows an ultrasensitive response for multi-analytes, such as Fe 3+, Hg 2+ and Cr 3+ . The limits of detection (LODs) of theFSOF for Fe 3+, Hg 2+ and Cr 3+ are in the range of 9.40 × 10 −10 –1.86 × 10 −9 . More importantly, the xerogel ofFSOF exhibits porous mesh structures, which could effect high-efficiency separation above metal ions from their aqueous solution, with adsorption percentages in the range 92.39–99.99%. In addition, by introducing metal ions into theFSOF, a series of metal ions coordinated supramolecular organic frameworks (MSOFs ) were successfully constructed. Moreover, MSOFs show selective fluorescence "turn on" ultrasensitive detection CN − (LOD = 2.12 × 10 −9 ) and H2 PO4 − (LOD = 1.78 × 10 −9 ). This is a novel approach to construct SOFs through a tri-pillar[5]arene-based foldamer, and also provides a new way to achieve ultrasensitive detection and high-efficiency separation.